Investigation of marine components of large direct seawater intake & brine discharge systems for desalination plants, towards development of a general design approach - Le Roux, Maria (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2010.